Systematic Review on Teaching and Learning for IoT Programming (International Journal of Innovative Computing, 2023)
Teaching and learning Internet of Things (IoT) programming is challenging. The literature regarding teaching and learning for IoT programming still lacking. Therefore, we conducted an updated and comprehensive review using a systematic literature review (SLR) to report recent research findings regarding teaching and learning for IoT programming. Five databases were selected for this SLR to identify related journals, of which 21 papers were reviewed systematically. This review answered five research questions regarding the level of study being taught for IoT programming; the tools used for IoT programming; the teaching and learning approach used; and the methods and instruments adopted for data collection.
Keywords: Internet of Things (IoT), systematic literature review, IoT programming